Ophthalmic genetics in South America. Issue 3 (28th August 2020) - Daich Varela, Malena; Moya, Rene; Schlottmann, Patricio G.; Hufnagel, Robert B.; Arberas, Claudia; Fernández, Federico M.; Inga, M. Eugenia; Lores, Juliana; Pachajoa, Harry; Prada, Carlos E.; Sallum, Juliana M. Ferraz
Abstract: South America comprises of heterogeneous topographies, populations, and health care systems. Therefore, it is not surprising to see differences among the countries regarding expertise, education, and practices of ophthalmic genetics for patients with rare eye diseases. Nevertheless, common challenges such as limited genetics training in medical schools and among ophthalmologists, scarcity of diagnostic tools for phenotyping, and expensive genetic testing not covered by the public healthcare systems, are seen in all of them. Here, we provide a detailed report of the current status of ophthalmic genetics, described by the personal views of local ophthalmologists from Brazil, Colombia, Argentina, and Chile. By reporting our strengths and weaknesses as a region, we intend to highlight the need for guidelines on how to manage these patients aligned with public health policies. Our region contributes to research worldwide, with thousands of well diagnosed patients from a number of unique and genetically diverse populations. The constant expansion of ophthalmic genetics and molecular diagnostics requires us to join forces to collaborate across South America and with other countries to improve access to next‐generation diagnostics and ultimately improve patient care.